Faktor-Faktor Yang Mempengaruhi Sikap Konsumen Pada Aplikasi Tiktok - Marianne Agustina Putri; Teguh Widodo (Cakrawala Repositori IMWI, 2023)
TikTok is a platform that is utilized by its users as a digital marketing medium. One of the TikTok accounts with the name @mbolangjatim is a unique icon that is used as digital marketing which contains various information about tourist attractions in the East Java area. This study aims to determine the factors that influence consumer attitudes in the @mbolangjatim marketing strategy. Based on an analysis of 100 content in the @mbolangjatim account, several digital marketing techniques were found, including advertising, storytelling, comedy, hashtags, feedback, and audio music. Advertising techniques are used to convey the latest brand promotions. Storytelling is known to have a positive influence on consumer confidence. Comedy can be an alternative that is implemented so that viewers don't feel bored watching @mbolangjatim content. Hashtags are used to increase the search and attention of TikTok users. Feedback can increase interaction and build consumer trust. Audio music has a positive effect on viral marketing efforts.